Digital disruption? Maternal mobile device use is related to infant social‐emotional functioning. Issue 4 (24th September 2017) - Myruski, Sarah; Gulyayeva, Olga; Birk, Samantha; Pérez‐Edgar, Koraly; Buss, Kristin A.; Dennis‐Tiwary, Tracy A.
Abstract: Mobile device use has become increasingly prevalent, yet its impact on infant development remains largely unknown. When parents use mobile devices in front of infants, the parent is physically present but most likely distracted and unresponsive. Research using the classic Still Face Paradigm (SFP) suggests that parental withdrawal and unresponsiveness may have negative consequences for children's social‐emotional development. In the present study, 50 infants aged 7.20 to 23.60 months ( M = 15.40, SD = 4.74) and their mothers completed a modified SFP. The SFP consisted of three phases: free play (FP; parent and infant play and interact), still face (SF; parent withdraws attention and becomes unresponsive), and reunion (RU; parent resumes normal interaction). The modified SFP incorporated mobile device use in the SF phase. Parents reported on their typical mobile device use and infant temperament. Consistent with the standard SFP, infants showed more negative affect and less positive affect during SF versus FP. Infants also showed more toy engagement and more engagement with mother during FP versus SF and RU. Infants showed the most social bids during SF and more room exploration in SF than RU. More frequent reported mobile device use was associated with less room exploration and positive affect during SF, and less recovery (i.e., engagement with mother, room exploration positive affect) during RU, even when controlling for individual differences in temperament. Findings suggest that the SFP represents a promising theoretical framework for understanding the impact of parent's mobile device use on infant social‐emotional functioning and parent–infant interactions. Abstract : In this study, we modified the traditional Still Face Paradigm (SFP) to include mobile device use, mimicking typical disruptions in parent–infant interactions that may occur in daily life. Patterns of child behavior during the modified SFP mirrored those of the traditional version, with infants showing the most distress when mothers were disengaged. Greater habitual parent device use was associated with less infant recovery following a disruption in a parent‐infant interaction. Findings provide support for the use of this modified paradigm as a framework for understanding the impact of parent's mobile device use on infant social‐emotional functioning and parent–infant interactions.